Target detectability in regional-scale AEM surveys. Issue 1 (1st December 2019) - Annetts, David; Hauser, Juerg
Summary: Direct detection of drillable targets is among the primary goals of airborne electromagnetic surveys. As larger government funded regional surveys move towards large (> 5 km) line spacings, it is natural to question the likelihood of such surveys of directly detecting orebodies. A natural subsequent question relates to the degree to which data from such surveys can characterise orebodies. Here we model a Tempest prospecting system and address the first question though a numerical modelling study of 1024 targets with all model parameters randomised. We show that the likelihood of target detection decreases with increasing line spacing. A generally-conductive regolith as it is common in Australia means that target detectability increases with increasing time. We show that while over 80% targets are detectable at 16.2 ms using a line spacing of 1 km, at most 24% of targets are detectable with a 10 km line spacing. We address target characterisation by inverting numerical modelling data. We show that is possible to recover correct parameters within a few percentage points for targets with strike lengths less than 6.5 km provided such targets are bisected by a flight line. Our results suggest that Tempest-based surveys with line spacing less than 2.5 km are required to detect discrete targets in a tenement and that surveys with a line spacing of 1 km are optimal when direct target detection is a survey goal.